Structural basis of the mechanism of β-methyl epimerization by enzyme MarH. Issue 44 (4th November 2019) - Liu, Bin; Hou, Yan; Wang, Xiaozheng; Ma, Xiaofang; Fang, Shiqi; Huang, Tao; Chen, Yanli; Bai, Zhiqiang; Lin, Shuangjun; Zhang, Rundong; Hu, Kaifeng
Abstract : Structures of free MarH and MarH in complex with l -Trp, the analogue of substrate, were determined and the mechanism of MarH-catalyzed stereospecific β-methyl epimerization was proposed. Abstract : Diverse derivatives of amino acids with different steric configurations are important biosynthetic building blocks. In biology, epimerization is an important way to generate steric diversity. MarH catalyzes the epimerization of the β-position of (3 R )-β-methyl-indolepyruvate (MeInPy), forming (3 S )-β-MeInPy. Both compounds are derivatives of l -tryptophan (l -Trp) and are important precursors of bioactive natural products. Here, we report the crystal structures of MarH and the NMR structure of its complex with l -Trp, an analogue of its native substrate, (3 R )-β-MeInPy. Structural analysis and mutagenesis studies indicated that His25 acts as a base to remove Hβ and generate a planar carbanion intermediate, which is then putatively reprotonated on the opposite face by a water molecule to form (3 S )-β-MeInPy in a stereospecific manner. The details of β-site isomerization at the atomic level provide deeper insights into the epimerization mechanism of MarH and will facilitate further enzyme design to extend the substrate scope.